Design and Fabrication of a New Model to Evaluate Analgesic, Antipyretic and Anti-inflammatory Action of a Drug - Dumbwani, Jacky; K. Jain, Neetesh (Journal of Neonatal Surgery, 2025)
The purpose of present study is based on the fact that many drugs have more than one action and evaluation of one action of a drug requires one whole screening model whereas for the evaluation of other action of same drug will require one more different screening model. In this study a new model has been fabricated for the evaluation of three different actions of one drug i.e. evaluation of analgesic, anti-inflammatory and antipyretic activity. Aspirin has analgesic, antipyretic, anti-inflammatory, and antiplatelet activity. Evaluation of all the activities of aspirin, we will require four different methods and models but in our study the newly fabricated model alone will be able to evaluate three actions of a single drug